1997
DOI: 10.1097/00002030-199711000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A potent activator of HIV-1 replication is present in the genital tract of a subset of HIV-1-infected and uninfected women

Abstract: This is the first study to show that a factor which can stimulate HIV-1 replication is present at biologically active levels in the reproductive tract of women. This factor could potentially affect sexual or vertical transmission of HIV-1 by altering genital tract virus load or virus expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
1
35
0
1
Order By: Relevance
“…Given the polymicrobial nature of BV, we cannot attribute the stimulatory effects of the CVLs to a specific bacterium or specific bacterial product. However, taken together, our previous observation that the HIV-LTR-inducing activity present in BV CVLs is protease-sensitive as well as the current demonstration that BV CVLs induce HIV LTR activation via TLR2 suggest that at least one of the stimulatory factors present in BV CVLs is either a lipopeptide or a glycoprotein (Spear et al, 1997). Although the TLR2/CD14 cell line experiments demonstrate that BV CVLs stimulate via TLR2, the role of CD14 in this stimulation has not been directly addressed by our studies.…”
Section: Discussionmentioning
confidence: 65%
“…Given the polymicrobial nature of BV, we cannot attribute the stimulatory effects of the CVLs to a specific bacterium or specific bacterial product. However, taken together, our previous observation that the HIV-LTR-inducing activity present in BV CVLs is protease-sensitive as well as the current demonstration that BV CVLs induce HIV LTR activation via TLR2 suggest that at least one of the stimulatory factors present in BV CVLs is either a lipopeptide or a glycoprotein (Spear et al, 1997). Although the TLR2/CD14 cell line experiments demonstrate that BV CVLs stimulate via TLR2, the role of CD14 in this stimulation has not been directly addressed by our studies.…”
Section: Discussionmentioning
confidence: 65%
“…If distinct viral evolution occurs in the PBMC and mucosal compartment, then viral factors could potentially explain the high mucosal susceptibility to HIV and SIV. Since viral replication and therefore genotypic evolution are driven by the inflammatory state of the infected cell, the dynamic inflammatory environment of the gastrointestinal mucosa may drive viral evolution to a greater extent than is seen in the peripheral blood compartment (41). Enhanced viral evolution at an inflamed mucosal site was suggested by Panther et al, who showed greater env heterogeneity in the female genital tract compared to paired blood samples (33).…”
Section: Ccr5mentioning
confidence: 99%
“…Consequently, vaginal secretions contain factors that may affect the infectiousness of HIV-1, as well as the ability to detect infectious virus. Although multiple factors in the vaginal tract could affect the MAGI assay (4,12,39,40), we were unable to demonstrate any effect on MAGI plaque formation with vaginal lavages from HIV-1-uninfected women or the addition of immune factors (proinflammatory cytokines and cathepsin D) often found in genital secretions. Other studies have indicated that GTIs such as bacterial vaginosis and infection with T. vaginalis may be associated with HIV-1 shedding and transmission.…”
Section: Fig 2 Analysis Of the Recovery Of Cell-free Infectious Virmentioning
confidence: 60%
“…To determine whether the number of MAGI plaques is proportional to the amount of infectious HIV- (2,4,12,39,40). To determine whether factors in normal vaginal lavages affect the MAGI assay, aliquots from 10 HIV-1-uninfected women were filtered and used in the MAGI assay in the absence of virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation